'Scaling' the academia: Perspectives of academics on the impact of their practices. Issue 3 (24th May 2021) - Kondakci, Yasar; Zayim-Kurtay, Merve; Kaya-Kasikci, Sevgi; Senay, Hanife Hilal; Kulakoglu, Busra
Abstract: The pressure on the universities to take a visible place in the rankings has caused anachronistic policies and practices in evaluating the performance of universities. The value attributed to the rankings results in policies prioritizing the criteria imposed by rankings while evaluating the performance of academics, which successively causes several issues in assessing the real impact of the academic practices. Considering these criticisms and concerns about the impact assessment, this study aimed at exploring the perceptions of academics about the impact of their academic practices. Adapting the interpretive phenomenological design, the data were collected through semi-structured interviews with 20 participants from the field of education in five flagship universities of Turkey. The findings of the study revealed that, although impact assessment understanding of the academics and their institutions go parallel with covering the practices around three basic missions of the university, many activities go in between without recognition by the same impact assessment practices. Interestingly, the academics exhibited their commitment to institutional policies in impact assessment practices; however, they exhibit resentment for the same policies due to failing to recognize the localized mission of the university, threatening the deeply rooted values of the academy, fouling the academy with ethical violations, and causing further detachment between academic practices and societal needs. The concerns and criticism of the current impact assessment are likely to alter the priorities of the universities and push them to adapt an impact assessment, which is less relevant to the local needs of their societies.